Visual processing of social context during mental state perception in schizophrenia - Green, Melissa J. (Canadian Medical Association, 2008)
OBJECTIVE: To examine schizophrenia patients' visual attention to social contextual information during a novel mental state perception task. METHOD: Groups of healthy participants (n = 26) and schizophrenia patients (n = 24) viewed 7 image pairs depicting target characters presented context-free and context-embedded (i.e., within an emotion-congruent social context). Gaze position was recorded with the EyeLink I Gaze Tracker while participants performed a mental state inference task. Mean eye movement variables were calculated for each image series (context-embedded v. context-free) to examine group differences in social context processing. RESULTS: The schizophrenia patients demonstrated significantly fewer saccadic eye movements when viewing context-free images and significantly longer eye-fixation durations when viewing context-embedded images. Healthy individuals significantly shortened eye-fixation durations when viewing context-embedded images, compared with context-free images, to enable rapid scanning and uptake of social contextual information; however, this pattern of visual attention was not pronounced in schizophrenia patients. In association with limited scanning and reduced visual attention to contextual information, schizophrenia patients' assessment of the mental state of characters embedded in social contexts was less accurate. CONCLUSION: In people with schizophrenia, inefficient integration of social contextual information in real-world situations may negatively affect the ability to infer mental and emotional states from facial expressions.